Comparison of different exercise ankle pressure indices in the diagnosis of peripheral artery disease. (December 2018) - Aday, Aaron W; Kinlay, Scott; Gerhard-Herman, Marie D
Although the resting ankle–brachial index (ABI) is commonly used as a tool to diagnose peripheral artery disease (PAD), several additional indices measured after exercise may have increased sensitivity for identifying PAD. The aim of this study was to determine the utility of resting ABI and three post-exercise physiological parameters for diagnosing PAD confirmed by arterial imaging studies. For each qualifying study, we assessed the performance measures for identifying PAD for resting ABI < 0.90, exercise ABI < 0.90, a decrease in ABI > 20% with exercise, and a decrease in ankle pressure > 30 mmHg with exercise. Of the 199 exams that met our inclusion criteria, imaging showed a > 75% stenotic lesion in at least one limb in 138 (69%) of patients. For stenoses > 75%, resting ABI < 0.90 had a sensitivity of 64% (95% CI: 56–72%) and exercise ABI < 0.90 had a sensitivity of 88% (95% CI: 82–93%). The sensitivity for a post-exercise ABI decrease > 20% was 67% (95% CI: 59–75%) and the sensitivity for a decrease in ankle pressure > 30 mmHg was 4% (95% CI: 2–9%). For individuals with a normal resting ABI but stenotic lesions > 75% confirmed by imaging ( n =49), the addition of exercise ABI testing correctly identified an additional 25% of this population. Overall, exercise ABI < 0.90 exhibits a greater sensitivity for detecting PAD compared to resting ABI. Furthermore, exercise ABI < 0.90 had added clinical utility in patients with normal resting ABIs and was superior to other commonly used exercise indices.